The Distribution Of Regulated Actomyosin States Is Central To Cardiac Muscle Regulation And Disturbance Of This Distribution Leads To Congenital Cardiomyopathies - Mathur, Mohit C. (East Carolina University, 2009)
Hypertrophic and restrictive cardiomyopathies are congenital cardiac diseases that have an incidence of over one in five hundred and may lead to sudden cardiac death. One of the main impediments to directed treatment is an incomplete understanding of the transition from mutation to disease morphology and hemodynamics, resulting in largely symptomatic treatment. This project sought to understand the molecular mechanisms related to muscle regulation that underlie the disease phenotype. We utilized an in vitro system with reconstituted myofilaments to determine the distribution of actomyosin states. We examined the effects of protein kinase C phosphorylation of troponin I using a glutamate mutation mimicking constitutive phosphorylation. We showed that this modification stabilized the inactive state of actin, without altering the rate of the active pathway. Shifting between actin states is a common method of altering myocardial regulation among a group of cardiomyopathy causing mutations. These mutations can shift the distribution between states to the active, inactive or intermediate state. We also showed that there is no change in the rate of the active pathway. Thus, the normal equilibrium is essential for proper cardiac muscle function, and any disturbance can lead to disease. We determined that there were three functional states of regulated actomyosin. Although there has been a widespread consensus that there are three structural states, there has been no evidence to show that each of these states has a unique function. Several of the mutations studied in this project provide evidence that there is a third functional state, and that stabilization of this state can lead to cardiomyopathy. We narrowed the parameters defining the third state. This state has an ATPase activity between 4-15% of the active state. Previous studies of the underlying molecular mechanism have not been able to explain changes in ATPase rates or find a common regulatory change. By determining the individual properties of each state along with their distributions in disease, this project advances the search for therapeutic agents that reverse the abnormal distributions, possibly reversing the changes seen in patient cardiac muscle by targeting the primary pathology.
Keywords: Biophysics, Medical; Chemistry, Biochemistry; Cardiac muscle regulation; Hypertrophic cardiomyopathy; Protein kinase C; Restrictive cardiomyopathy; Tropomyosin; Troponin; Biochemistry; Cardiomyopathies--prevention & control; Heart Diseases; Biophysics--methods